The Politics of Education Policymaking in Nepal - Dhakal, Rebat Kumar (Journal of Education and Research, 2019)
I begin this editorial with an assertion that the contemporary public policymaking landscape in Nepal shows little citizens’ participation and thus education policymaking also bears a similar approach. Here, public policies refer to “the decisions and actions of government and the intentions that determine those decisions and actions” (Geurts, 2011, p. 6). Theoretically, governments across the globe in recent decades have committed for larger citizen participation in public policymaking. Therefore, I understand public policymaking as a phenomenon in which wider stakeholders engage in governmental decision-making processes aimed at addressing a public issue.